Del Mediterráneo al Atlántico. Mercaderes en la urbes (Siglos XVI-XVII) - García Bernal, José Jaime; Guillaume-Alonso, Araceli; Perez, Béatrice; Zerari, Maria (Studia Historica: Historia Moderna, 2020)
.